Biochemical blood counts in the application of fish oil preparations in conditions of intense physical activity - E. A. Knyazeva; A. V. Deryugina; P. V. Yastrebov; G. А. Boyarinov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2025)
The objective was to evaluate the effect of fish oil and ozonated fish oil in the dynamics of biochemical parameters of blood plasma while modeling physical activity up to “to failure” in rats.Methods and materials. The animals were divided into 4 groups of 16 rats. Saline was administered orally to control animals (group 1). Rats (group 2) were fed fish oil (dose 35 mg/kg) (FO), rats of group 3 received ozonated fish oil (dose 35 mg/ kg, ozonide number 3000) (OFO 3000), group 4 – ozonated fish oil (dose 35 mg/ kg, ozonide number 1500) (OFO 1500). Physical activity was simulated by the method of forced swimming of rats «to failure» with a load of 10 % of body weight. Blood sampling was performed from the hyoid vein 6 times: the initial level of indicators was determined, after stress tests (4 times) and after drug withdrawal (on day 3). The blood samples were assessed for glucose, lactate, urea, creatinine, AST, ALT.Results. Physical activity caused a decrease in glucose concentration in all groups at the stages of loading tests with its subsequent recovery after drug withdrawal. The use of OFO 3000 showed exclusion because the index remained decreased after the drugs cancellation. Physical activity in the control group was accompanied by the most pronounced increase in lactate. The use of FO and OFO 1500 levelled the increase in lactate compared to the control group. The concentration of urea increased in the control group, with the action of FO, OFO 3000 and remained at the level of initial values with the use of OFO 1500. The concentration of creatinine increased in all groups, the least pronounced at the action of use of FO and OFO 1500. Creatinine concentration increased most strongly with OFO 3000 and did not recover after drug withdrawal. AST and ALT after physical activity increased at stages after exercise tests in all groups. However, with the use of FO and OFO 1500, a decrease in indices by the 4th exercise test and a pronounced recovery after drug cancellation were observed.Conclusion. Oral administration of OFO 1500 with physical exertion of significant intensity to a greater extent caused the preservation of muscle tissue and a reduction in the recovery time of the body after excessive physical exertion «to failure».